2016
DOI: 10.1002/adma.201505375
|View full text |Cite
|
Sign up to set email alerts
|

Multilayered Graphene Hydrogel Membranes for Guided Bone Regeneration

Abstract: A multilayered graphene hydrogel (MGH) membrane is used as an excellent barrier membrane for guided bone regeneration. The unique multilayered nanostructure of the MGH membrane results in improved material properties, which benefits protein adsorption, cell adhesion, and apatite deposition, and allows higher quality and fast bone regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
127
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(127 citation statements)
references
References 48 publications
(38 reference statements)
0
127
0
Order By: Relevance
“…Exploiting this unique property, the rGO hydrogel was tested as artificial barrier membrane for guided bone regeneration in a rat calvarial defect model, in which the membrane successfully maintained osseous space, promoted osteodifferentiation and mineralization, and achieved higher quality and fast bone regeneration (Figure 12D). Inspired by these reports, studies using rGO to improve properties of bioceramics (i.e., HA) based BTE scaffolds have been recently reported. Unlike GO, the effects of rGO on the hydrophilicity of scaffolds were generally not discussed, presumably because the effects were not obvious due to the reduced oxygen content.…”
Section: Carbon‐based Nanomaterials For Bone Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Exploiting this unique property, the rGO hydrogel was tested as artificial barrier membrane for guided bone regeneration in a rat calvarial defect model, in which the membrane successfully maintained osseous space, promoted osteodifferentiation and mineralization, and achieved higher quality and fast bone regeneration (Figure 12D). Inspired by these reports, studies using rGO to improve properties of bioceramics (i.e., HA) based BTE scaffolds have been recently reported. Unlike GO, the effects of rGO on the hydrophilicity of scaffolds were generally not discussed, presumably because the effects were not obvious due to the reduced oxygen content.…”
Section: Carbon‐based Nanomaterials For Bone Tissue Engineeringmentioning
confidence: 99%
“…B) Schematic illustration of the cross‐section of the rGO hydrogel membrane with trapped water molecules and the highly densified structure after the removal of water molecules by drying. Adapted with permission . Copyright 2016, Wiley‐VCH.…”
Section: Carbon‐based Nanomaterials For Bone Tissue Engineeringmentioning
confidence: 99%
“…During regeneration, the barrier membrane provides a sealed space that allows bone regeneration, rather than internal growth of connective tissue 30) . The success of GBR, which is reflected by a higher regenerative potential relative to unsupported healing conditions, depends on the properties of the barrier membrane materials, particularly their interactions with osseous and surrounding tissues 31) . The membrane materials should exhibit mechanical properties compatible with bone tissue 32) , which means that the membrane requires sufficiently strong and balanced mechanical strength to maintain the space for bone regeneration during the healing process 33) .…”
mentioning
confidence: 99%
“…[19,21,31,32] Many scholars have reported that the physical properties of the substrates can regulate the pluripotency of ESCs. [19,21,31,32] Many scholars have reported that the physical properties of the substrates can regulate the pluripotency of ESCs.…”
Section: Discussionmentioning
confidence: 99%